(9-3i)-(2+i)=

Simple and best practice solution for (9-3i)-(2+i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9-3i)-(2+i)= equation:


Simplifying
(9 + -3i) + -1(2 + i) = 0

Remove parenthesis around (9 + -3i)
9 + -3i + -1(2 + i) = 0
9 + -3i + (2 * -1 + i * -1) = 0
9 + -3i + (-2 + -1i) = 0

Reorder the terms:
9 + -2 + -3i + -1i = 0

Combine like terms: 9 + -2 = 7
7 + -3i + -1i = 0

Combine like terms: -3i + -1i = -4i
7 + -4i = 0

Solving
7 + -4i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -4i = 0 + -7

Combine like terms: 7 + -7 = 0
0 + -4i = 0 + -7
-4i = 0 + -7

Combine like terms: 0 + -7 = -7
-4i = -7

Divide each side by '-4'.
i = 1.75

Simplifying
i = 1.75

See similar equations:

| -6(7y-2)=31+9y | | 1+2x=2(x+2)-3(1x-4) | | -6=3t-36 | | 4t(6*6)/78t=567 | | 8n+32=2n-8 | | 4t(6*6)/78t= | | -25/24=-2/3-3/2n | | -310=5(7a-6) | | 31+8v=-1+7(3v-1) | | 11-(x/4)=-23 | | 9/4=f/28 | | 1+6a=-11+3a | | 8x+7=8+3x | | 19=-6+8(f-4) | | 265v^2+289=0 | | x-7=13-3x | | 8p-56=9p+10 | | rt-2n=yfort | | 3y(2y+1)+2y(y+6)=25 | | 9x^2-103x+328=0 | | 4x+3=7x-19 | | 3y(2y+1)+2y(y+6)= | | 180=2x-5+4x+10 | | 2+5/x-4 | | 3d-34.56=17.01 | | =3y(2y+1)+2y(y+6) | | 3x+10+5=180 | | 18-2n+2=4n+8 | | (13t/42)-(t/7)=1 | | -4-8=-5+x | | 3(2x+5)+2(3x+2)=24 | | r/.4=.8 |

Equations solver categories